Pemaknaan Motif Truntum Batik Surakarta: Kajian Semiotik Charles W. Morris - Widodo, Widodo; Soekarba, Siti Rohmah; Kusharjanto, Bram (Sutasoma : Jurnal Sastra Jawa, 2021)
Batik is an artistic culture inherited from the ancestors of the Indonesian people which has noble values, has become the pride of the Javanese. This paper describes the meaning of the Surakarta batik Truntum motif in the semiotic study of Charles W. Morris and Frued's psychoanalytic analysis. Morris semantics are used to find the meaning behind the Surakarta batik Truntum motif: Tanjung flower motifs, stars, gurdho (garuda), rhombuses, and colors. Meanwhile, Freud's id is applied to the meaning of sexual desire for the perpetrator in the process of creating motives. The methodology used is multidisciplinary, combining historical approaches, semiotics, and cultural studies. The results of the analysis show that Trumtum batik as a noble art has crossed a long time and has a dialectic with cultural developments. The Trumtum motif is a unification of symbols which are interpreted in spiritual syncretism. Ratu Kencana (Beruk) in lamenting loneliness, sadness, and loneliness manifests itself through the distribution of 'id' and 'sublime' into Truntum batik art. Keywords: Truntum Motif, Meaning, Semiotics, Morris, Culture